Fontes de nitrogênio na fisiologia de cultivares de café arábica sob aumento da concentração de CO2 - Carvalho, Pollyanna Aparecida de (2020)
This study aimed to evaluate physiological changes in coffee plantlets (‘Mundo Novo’, ‘Rubi’ and ‘Catuaí’) grown under high CO2 concentration and subjected to nitrate (NO3-) or ammonium (NH4+) application. The treatments consisted of nutrient solution application with 16 mM NO3- or 16 mM NH4+ under atmosphere with current CO2 concentration (380μL CO2 L-1 air) or under atmosphere enriched with 760μL CO2 L-1 air. Growth, carbohydrate metabolism, nitrogen assimilation, mineral content and antioxidant system activity, were analyzed. The results showed that the factors CO2 concentration (380 or 760 μL. L-1) and nitrogen source (NO3- or NH4+), influenced the physiological processes of Coffea arabica cultivars (‘Mundo Novo’, ‘Rubi’ and ‘Catuaí’) at different levels, according to the analyzed response. The interaction between these two factors also was significant for several variables evaluated. The increase in [CO2] increased net assimilation rate and water use efficiency, on the other hand, reduced stomatal conductance and transpiratory rate. The chlorophylls levels, the Fv/Fm ratio, the respiratory rate and the Vcmax and Jmax parameters were also positively influenced by the high [CO2], while photorespiration was reduced. Coherently, the relative growth rate and the dry matter of the plants increased significantly under higher [CO2]. It was also found that, in the coffee leaves, the treatment with high [CO2] reduced soluble carbohydrates amounts while increasing starch contents, still in the leaf tissues, the highest [CO2] implied in reductions in the nitrate reductase (RN) and glutamine synthetase (GS) activities with consequent drops in amino acids regardless nitrogen source. Proteins concentrations decreased in the leaves of the plants with NO3- and increased in the plants treated with NH4+. The macronutrients levels and antioxidant system activity also showed reductions in the leaves of the plants under high CO2 in all treatments. In the roots, the increase in [CO2] increased soluble carbohydrates amounts, as well as the invertase activity, even in this tissue, the highest [CO2] implied increases in the NO3- and NH4+ levels, and RN and GS activities with consequent increases in the amino acids and proteins concentrations. The greatest results of GS activity and protein production were detected in the treatment with NH4+. Antioxidant system activity also increased in the roots of plants under high [CO2] regardless nitrogen source. It was found that, under high [CO2], the plants treated with NH4+ outperformed the plants with NO3- because, the plants with NH4+, showed photosynthetic rates and water efficiency use higher resulting in greater matter dry accumulation. Thus, in general, from the increase in [CO2], for the specie, favorable changes were verified. In addition, the NH4+ application was more favorable, for the physiological performance of the coffee plant under high [CO2] than NO3- application.